Ameliorated polyvinylidene fluoride based proton exchange membrane impregnated with graphene oxide, and cellulose acetate obtained from sugarcane bagasse for application in microbial fuel cell. Issue 6 (December 2021) - Sharma, Mukesh; Das, Pranjal P.; Sood, Trishla; Chakraborty, Arun; Purkait, Mihir K.
Abstract: Polyvinylidene fluoride (PVDF) based, Cellulose acetate (CA), and Graphene oxide (GO) doped membrane acts as a superior cost-effective cation exchange membrane (CEM) for the energy extraction application using microbial fuel cells (MFCs). In this study, the waste sugarcane bagasse was used to prepare CA, and the Tour method was used to prepare GO. CA and GO compositions were varied to prepare CEMs WCA-1, WCA-2, WCA-3, and WCA-4. Doping the functionalized GO material in the hydrophilic membranes enhances the contribution of conducting phase concerning its hydrophilic nature and facilitates its functional characteristics at the surface. Further, adding an adequate amount of GO improves the physicochemical properties of the membrane and its mechanical stability. Also, with the fusion of GO in the membrane, the trend for water uptake ability significantly increases. Post sulfonating the prepared membranes the enhancement in the attained proton conductivity values from 0.025 Scm -1 for WCA-1 to 0.4 Scm -1 for WCA-4 was observed, which may be attributed to the increase in the GO content in the prepared membranes. Among various prepared membranes, WCA-3 was considered for MFC application. The WCA-3 membrane outperformed several membranes for wastewater treatment and energy extraction using MFC. Columbic efficiency (CE) of 7.1%, chemical oxygen demand (COD) removal efficiency of 97.5 ± 0.8%, and power density of more than 150.22 mW m −2 were achieved without any electrode modification. Thus, the prepared low-cost novel PVDF-based, GO and CA membrane (WCA-3) elucidated its appropriateness for proliferating the efficacy of MFC and is recommended for scaling up of MFCs. Graphical abstract: ga1 Highlights: Novel high performance cation exchange membrane is prepared. Achieved power density of 150.22 mW m −2 without modification of electrode. High proton conductivity of 0.4 Scm -1 was achieved for the prepared membrane. Functionalized GO and CA in the hydrophilic substrate enhance the functional characteristics of the membrane surface. Better results can be achieved implementing catalyst and electrode modifications.